2016
DOI: 10.3892/or.2016.4884
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of MCT1 and PFKFB3 influences cell proliferation and apoptosis in bladder cancer by altering the tumor microenvironment

Abstract: Abstract. Phosphofructokinase-2/fructose-2,6-bisphosphatase 3 (PFKFB3) and monocarboxylate transporter 1 (MCT1) play important roles in tumor endothelial cells (ECs) and several biological processes. The present study was conducted to study the effects of PFKFB3 and MCT1 on cell proliferation and apoptosis in the tumor microenvironment by co-culture of HUVECs and T24, a bladder cancer (BC) cell line, using a microfluidic device. Immunofluorescence assay showed that HUVEC activity was significantly enhanced und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…Our previous studies revealed a series of changes of metabolic reprogramming in the context of tumor microenvironment. We found that CAFs and tumor endothelial cells in tumor microenvironment played an important role in cancer glycolysis and progression 11 , 20 . Targeting MCT1 in CAFs and tumor endothelial cells regulated BCa cell growth and apoptosis by altering the tumor microenvironment 20 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our previous studies revealed a series of changes of metabolic reprogramming in the context of tumor microenvironment. We found that CAFs and tumor endothelial cells in tumor microenvironment played an important role in cancer glycolysis and progression 11 , 20 . Targeting MCT1 in CAFs and tumor endothelial cells regulated BCa cell growth and apoptosis by altering the tumor microenvironment 20 .…”
Section: Discussionmentioning
confidence: 89%
“…We found that CAFs and tumor endothelial cells in tumor microenvironment played an important role in cancer glycolysis and progression 11 , 20 . Targeting MCT1 in CAFs and tumor endothelial cells regulated BCa cell growth and apoptosis by altering the tumor microenvironment 20 . The present study found that knockdown of MCT1 in BCa cells significantly inhibited cell proliferation in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 89%
“…PFKFB3, a member of the PFKFB family, has a significantly high kinase activity, enhances the F2,6BP level and glycolysis effect ( 12 ). The protein levels of PFKFB3 are commonly elevated in various types of human cancer, including breast ( 13 ), gastric ( 14 ) and bladder cancer ( 15 ). In addition, previous studies have demonstrated that the inhibition of PFKFB3 was able to suppress the glucose metabolism and cell proliferation in cancer cells ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results are interesting and unexpected. When tumor cells coexist with vascular endothelial cells in hypoxic and acidic environments, the energy metabolic pathway of glycolysis is activated, which is critical for tumor growth and angiogenesis [12]. Glycolysis is enhanced by MCT1 and MCT4, and therefore, reprogramming of glucose metabolism occurs [11].…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg effect describes a new metabolic way in which most cancer cells function utilizing energy generated from efficient glycolysis followed by the fermentation of lactic acid and acidification [12, 13]. Enhanced glycolysis is tightly associated with tumorigenesis and metastasis [13].…”
Section: Introductionmentioning
confidence: 99%